The effect of online customer review and online customer rating on the trust and interest of consumer purchases - Purwantoro Purwantoro; Yulfita Aini; Hidayat Hidayat; Arrafiqurrahman Arrafiqurrahman; Andi Afrizal (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to see how the influence of online customer reviews and online customer ratings on the trust and interest of consumers in the purchase of Sialang Jaya Village. The population in this study is the community in Sialang Jaya Village. The research sample used probability sampling as many as 100 people. The independent variables in this study are online customer reviews (X1), online customer ratings (X2), trust (Y1) and purchase interest variables (Y2). Methods of data collection using questionnaires and library research. Data analysis using path analysis using the SmartPLS 3 program. The results obtained from this study are that both reviews and ratings have a proven relationship to customer purchase interest and are an important feature, but not a factor that causes increased customer confidence. Online customer review indirectly does not affect buying interest through trust, and online customer rating indirectly has a positive effect on buying interest through trust.